Situace v zemědělství a postavení rolnictva na území západního Běloruska během 20. let 20. století - Marková, Alena (Lidé města, 2009)
The given paper addresses to study the phenomena of the fruitful connection between the political movement and the economic situation of peasants in Western Belarus during the 1920s, when agitation of the radical left achieved major success. In this study, we follow the discursive background of the key factors in the growth of the national movement during this short time period. The article aims at providing an explanation of the specific circumstances and at presenting that in the case of Western Belarus, the main role in the mass mobilization of the local population was played by socio-economic factors. National oppression (denial of Belarusian schools, forced polonisation, assimilation efforts from the Polish side) linked with social and economic oppression, led to the unusually accelerated progress of the Belarusian national movement.